2006
DOI: 10.1159/000093856
|View full text |Cite
|
Sign up to set email alerts
|

Scleromyxedema, a Positive Effect with Thalidomide

Abstract: Scleromyxedema is a rare dermatological disorder marked by widespread symmetric 2- to 3-mm, firm, waxy, closely spaced papules involving the hands, forearms, face, neck, upper trunk and thighs. The most common extracutaneous manifestation of scleromyxedema is a benign plasma cell dyscrasia. Treatment of scleromyxedema is limited by the lack of long-term results, toxicity and significant adverse side effects. We report a severe case of scleromyxedema who had marked improvement when treated with thalidomide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…The majority of patients with scleromyxedema have a concomitant monoclonal gammopathy of unknown significance. The serum of these patients has been shown to induce fibroblast proliferation in vitro, as well as increase fibroblast production of hyaluronic acid and prostaglandin E; however, the purified immunoglobulin alone does not induce these effects in vitro [14,15]. The level of paraproteinemia does not correlate with skin or systemic findings [14,15].…”
Section: To the Editormentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of patients with scleromyxedema have a concomitant monoclonal gammopathy of unknown significance. The serum of these patients has been shown to induce fibroblast proliferation in vitro, as well as increase fibroblast production of hyaluronic acid and prostaglandin E; however, the purified immunoglobulin alone does not induce these effects in vitro [14,15]. The level of paraproteinemia does not correlate with skin or systemic findings [14,15].…”
Section: To the Editormentioning
confidence: 99%
“…The serum of these patients has been shown to induce fibroblast proliferation in vitro, as well as increase fibroblast production of hyaluronic acid and prostaglandin E; however, the purified immunoglobulin alone does not induce these effects in vitro [14,15]. The level of paraproteinemia does not correlate with skin or systemic findings [14,15]. It has been suggested that the paraproteinemia may be a response to an unknown inciting factor and not the cause of disease manifestations.…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…Case reports cite variable improvement with other immunosuppressants including cyclophosphamide and cyclosporine (65)(66)(67)(68). There are multiple cases describing some benefit using thalidomide, although there remains a legitimate concern for the development of disabling peripheral neuropathy (68)(69)(70)(71)(72). More recent data note benefit of autologous stem cell transplantation in recalcitrant cases (53,(73)(74)(75).…”
Section: Treatment and Prognosismentioning
confidence: 99%